THE POTENTIAL OF SORGHUM BICOLOR L. AS A BLOOD GLUCOSE LOWERING AGENT : A REVIEW - Dwi Wahyuni Leboe; Nur Syamsi Dhuha; Munifah Wahyuddin; Nur Rezky Rutami A (Universitas Islam Negeri Alauddin Makassar, 2020)
The increasing mortality rate in Indonesia due to diabetes mellitus is a health problem in the world, especially in Indonesian. Evidenced by prevalence of diabetes mellitus which increases every year and is estimated in 2030 achieved 21,3 million according by WHO. Pharmacological therapy which cost is relatively expensive and can caused side effects from the use of chemical drugs. For this reason, the importance of finding new alternative therapy. Sorghum bicolor L. is a cereal that has high nutritional value and phytochemical compounds. This research purpose to know contain of Sorghum bicolor L. and the mechanisme Sorghum bicolor L. as a blood glucose lowering agent. In this research is the literature study method based on primary and secondary data obtained. The database obtained is from Google scholar, Science direct, Research gate, NCBI, MDPI by using keywords. And the analysis of 43 journals obtained were scanned and analyzed in more detail by introduction, method, result, and conclusion of each journal . And the made in the data analysis table. Shows that Sorghum bicolor L. can be used as a blood glucose lowering agent because contain antidiabetic compounds, namely is phenolic compounds of phenolic acid, flavanoids, and tannin. And has a low glycemic index value and high fiber. Which can provide hypoglycemic effects and reduce postprandial blood glucose levels because it a slor digestion, slow gastric emptying, can inhibit the activity of digestive enzymes, namely the activity of α-glucosidase and α- amylase, increasen insulin sensitivity, and inhibits the process of glucogenesis in the liverblood pressure, broken bones, diabetes, malaria, ulcers, vomiting blood, bleeding, appendicitis and lungs.